PENGONTROLAN ENERGI PANAS DAN KELEMBABAN MENGGUNAKAN SENSOR DHT22 DAN ESP32 PADA PROSES FERMENTASI TEMPE GEMBUS - Musa, Wahab; Hidayat, Ikhsan; Alam, Saiful; Asmara, Bambang Panji; Tolago, Ade Irawati (Journal Of Renewable Energy Engineering, 2024)
The fermentation process of tempe embus with conventional methods is highly dependent on weather conditions and requires heat energy (temperature) 25°C - 35°C within 36 - 48 hours. This research aims to stabilize the heat energy and reduce the fermentation process time to get quality tempeh production results in a short time. The research method used is the experimental method by making an automatic temperature and humidity controller and testing its performance. This tool works using the DHT22 sensor and ESP32 microcontroller as the control center. Temperature automation is done with two conditions that are used to regulate lights and fans. If the fermentation temperature is lower than the setpoint, the lower light and upper light turn on, if the temperature rises, the upper light turns off and the fan turns on, to keep the temperature within the pre-set setpoint value. This research shows that the temperature and humidity control device operates stably in the temperature range of 32°C to 35°C. At these temperature conditions, the fermentation process runs stably. At that temperature condition, the fermentation process of tempe embus lasts 16 hours, with testing of color, taste, and smell for the best quality category Tempe.